Rapid metabolic discrimination and prediction of dioscin content from African yam tubers using Fourier transforminfrared spectroscopy combined with multivariate analysis - Kwon, Y.K.; Jie, E.Y.; Sartie, A.M.; Kim, D.J.; Liu, J.R.; Min, B.W.; Kim, S.W. (Elsevier, 2015)
To determine whether or not FT-IR spectroscopy could be used for taxonomic and metabolic discriminationof African yam lines, tuber samples from African and Asian yam species were subjected to FT-IR.Most remarkable spectral differences between African and Asian yams were found in the 1750–1700 cm 1 region, polysaccharide (1200–900 cm 1) and protein/amide I and II (1700–1500 cm 1) regionsof FT-IR spectra. A hierarchical dendrogram based on partial least square-discriminant analysis (PLS-DA)of FT-IR data from 7 African yam species show phylogenetic relationship. In addition, the content of dioscin,a steroidal saponin found in yam tuber, was predicted using a PLS regression model with regressioncoefficient R2 = 0.7208 indicated that prediction model had average accuracy. Thus, considering theseresults we suggest that FT-IR combined with multivariate analysis could be applied as a novel tool formetabolic evaluation and high-throughput screening of African yam lines with higher content of dioscin.